2011
DOI: 10.1017/s0305000910000619
|View full text |Cite
|
Sign up to set email alerts
|

Contending with foreign accent in early word learning*

Abstract: By their second birthday, children are beginning to map meaning to form with relative ease. One challenge for these developing abilities is separating information relevant to word identity (i.e. phonemic information) from irrelevant information (e.g. voice and foreign accent). Nevertheless, little is known about toddlers' abilities to ignore irrelevant phonetic detail when faced with the demanding task of word learning. In an experiment with English-learning toddlers, we examined the impact of foreign accent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 34 publications
4
60
1
Order By: Relevance
“…Instead, children reacted to mispronounced newly-learned words as though they were not the words learned during training. This contrasts with the results of Schmale et al (2011), who found that younger children (30 months) readily generalized to an accented word-form. On the face of it, it is puzzling that older children do not show better performance.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Instead, children reacted to mispronounced newly-learned words as though they were not the words learned during training. This contrasts with the results of Schmale et al (2011), who found that younger children (30 months) readily generalized to an accented word-form. On the face of it, it is puzzling that older children do not show better performance.…”
Section: Discussioncontrasting
confidence: 99%
“…In Experiment 1, children learned words in one accent and were then tested on the original accent and an altered accent. This simulated learning in one accent, followed by generalization to never-before-heard accent-variants (see Schmale et al, 2011, for a related approach). (Note that the term "accent variant" is used here to mean a word form produced in a particular accent, rather than a particular accent such as southeastern U.S.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…By 2.5 years, children no longer need accent exposure for recognizing familiar words (Van Heugten & Johnson, in press) or newly-learned words (Schmale, Hollich, & Seidl, 2011). Interestingly, the children in the Van Heugten and Johnson (in press) study were more successful at recognizing the accented words (that is, they fixated the named picture more robustly) when words were embedded in full-sentence contexts, hinting that at least one sort of context-acoustic-phonetic sentential context-may facilitate accent comprehensions.…”
mentioning
confidence: 99%